DEVELOPING A MEASURE OF LOCAL GOVERNMENT’S FINANCIAL CONDITION - Irwan Taufiq Ritonga (Faculty of Economics and Business, Universitas Gadjah Mada, 2014)
This study develops an instrument to measure the financial condition of local governments (LG) in Indonesia. The instrument will serve as an early warning system for local governments’ financial management. The instrument to measure their financial condition consists of six dimensions, namely short-term solvency, long-term solvency, budgetary solvency, service-level solvency, financial flexibility, and financial independence. Each dimension has its own indicators. There are a total of eighteen indicators examined in this study. These indicators are combined to form a composite index, called a Financial Condition Index (FCI). The reliability and validity of the composite index is analyzed and the results show that the measures developed in this study are reliable and valid. In addition, the instrument possesses the criteria of a good measure: it is theoretically sound, a comprehensive assessment, it has predictive ability, distinctive ability, it is practical, objective, and a resistant to manipulation and gaming.